Utility of Lymphoblastoid Cell Lines for Induced Pluripotent Stem Cell Generation - Satish Kumar; Joanne E. Curran; David C. Glahn; John Blangero (Stem Cells International)
A large number of EBV immortalized LCLs have been generated and maintained in genetic/epidemiological studies as a perpetual source of DNA and as a surrogate in vitro cell model. Recent successes in reprograming LCLs into iPSCs have paved the way for generating more relevant in vitro disease models using this existing bioresource. However, the overall reprogramming efficiency and success rate remain poor and very little is known about the mechanistic changes that take place at the transcriptome and cellular functional level during LCL-to-iPSC reprogramming. Here, we report a new optimized LCL-to-iPSC reprogramming protocol using episomal plasmids encoding pluripotency transcription factors and mouse p53DD (p53 carboxy-terminal dominant-negative fragment) and commercially available reprogramming media. We achieved a consistently high reprogramming efficiency and 100% success rate using this optimized protocol. Further, we investigated the transcriptional changes in mRNA and miRNA levels, using FC-abs ≥ 2.0 and FDR ≤ 0.05 cutoffs; 5,228 mRNAs and 77 miRNAs were differentially expressed during LCL-to-iPSC reprogramming. The functional enrichment analysis of the upregulated genes and activation of human pluripotency pathways in the reprogrammed iPSCs showed that the generated iPSCs possess transcriptional and functional profiles very similar to those of human ESCs.